Sfera B + R jako element systemu innowacyjnego w gospodarce opartej na wiedzy - Jaworska, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The investment in knowledge and R&D zone is the basic of economy development, professions creation as well as the standard of living increase. Science, technology and innovation have become key factors contributing to economic growth in both advanced and developing economies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 180-189